Internalization Of Tolerance Values In The Al-Kafirun Surat Verse 6 And The Al-Baqarah Surat Verse 256 In Forming Moderate Attitudes Of Students At Muhammadiyah Vocational School Berau - Khamam Khosiin; Weny Alpina; Benny Prasetya (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the internalization of Qur’anic tolerance values in shaping students’ moderate attitudes at SMK Muhammadiyah Berau. The study focuses on the values contained in QS. Al-Kafirun verse 6 and QS. Al-Baqarah verse 256 as theological foundations for religious tolerance, respect for difference, and rejection of coercion in matters of faith. This research used a qualitative case study approach. Data were collected through in depth interviews, classroom observation, and document analysis involving Islamic Religious Education teachers, school leaders, students, and parents. The findings show that the internalization process occurs through Islamic Religious Education learning, teacher role modeling, dialogic discussion, school culture, student activities, and daily habituation. PAI teachers play a central role as interpreters of Qur’anic values, facilitators of dialogue, and moral examples for students. Supporting factors include the school’s vision, Muhammadiyah religious culture, teacher commitment, anti-bullying policy, student activities, peer interaction, and family support. However, several obstacles remain, such as students’ uneven understanding of tolerance, social media influence, rigid family backgrounds, limited learning time, and the persistence of jokes that may demean religious identity. The study concludes that Qur’anic tolerance values contribute to students’ moderate attitudes, especially in respecting differences, rejecting coercion, communicating ethically, cooperating with peers, and solving conflicts peacefully.